Effect of Radiation on Magnetohydrodynamic Free Convection Boundary Layer Flow on a Solid Sphere with Newtonian Heating - Alkasasbeh, Hamzeh Taha; Mohd Zuki, Salleh; Razman, Mat Tahar; Roslinda, Nazar (2013)
In this paper, the effect of radiation on magnetohydrodynamic free convection boundary layer flow on a solid sphere with Newtonian heating, in which the heat transfer from the surface is proportional to the local surface temperature, is considered. The transformed boundary layer equations in the form of partial differential equations are solved numerically using an implicit finite difference scheme known as the Keller-box method. Numerical solutions are obtained for the local wall temperature, the heat transfer, and the local skin friction coefficient, as well as the velocity, and temperature profiles. The features of the flow and heat transfer characteristics for various values of the Prandtl number Pr, magnetic parameter M, radiation parameter N, the conjugate parameter R and the coordinate running along the surface of the sphere, x are analyzed and discussed.